The ethnic identity of transracially placed foster children with an ethnic minority background: A systematic literature review. (2nd February 2021) - Degener, Clementine J.; van Bergen, Diana D.; Grietens, Hans W. E.
Abstract: Background: Ethnic minority foster children are frequently placed in families with ethnic majority backgrounds. In the international literature these placements are most commonly called transracial placements. Aims: With this study, we aim to obtain an encompassing view of the empirical scientific literature on how transracial placements may affect the ethnic identity of foster children. Materials and methods: To gain insight into the ethnic identity of transracially placed foster children and the way they are ethnically socialized, we conducted a systematic literature review. We thereby followed the guidelines of the PRISMA statement. Results: Transracially placed foster children may experience higher fluctuations in their racial/ ethnic identity over time than adolescents with a minority background in the general population. They also seem to be prone to experience disconnection from, or on the contrary, connection with the birth network; and some transracially placed foster children struggle with societal messages they receive about minority ethnicity and race. They may have an increased awareness of their minority ethnic background because of different physical appearances between themselves and the foster family. Foster parents can play a pivotal role in these processes, since culturally competent foster parents may guide foster children in their ethnic identity development by being open towards children's cultural minority background as well as being self‐reflective regarding their own cultural values and beliefs. Discussion: The ethnic development of transracially placed foster children seems to be influenced by intersecting mechanisms of being in foster care and having a minority ethnicity. Although the selected articles assume that foster parents impact the ethnic identities of their ethnic minority foster children, none of them measured the impact of foster parents' skills and knowledge on foster children' s ethnic identity development directly. Conclusion: Being transracially placed impacts the ethnic identity of foster children. Foster parents need to be cultural competent to encourage their foster children's ethnic identity development.